2008
DOI: 10.1007/s12221-008-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of artificial neural network and linear regression models for prediction of ring spun yarn properties. I. Prediction of yarn tensile properties

Abstract: In this study artificial neural network (ANN) models have been designed to predict the ring cotton yarn properties from the fiber properties measured on HVI (high volume instrument) system and the performance of ANN models have been compared with our previous statistical models based on regression analysis. Yarn count, twist and roving properties were selected as input variables as they give significant influence on yarn properties. In experimental part, a total of 180 cotton ring spun yarns were produced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…ANNs have been used successfully as a predicting tool in all areas of textiles from fibre to complex composites. In textile spinning domain ANNs have been used to detect and classify trash particles in cotton web [6], control of draw frame sliver evenness and levelling action point from machine and material parameters [7], optimisation of spinning process at ring frame using draw frame parameters [8], the prediction of ring spun cotton yarn properties from HVI (high volume instrument) characteristics of fibres [9], comparison of ANN and regression models for yarn hairiness, evenness and tensile properties using fibre HVI properties, roving properties, yarn count and twist multiplier [10,11]. Apart from ring spinning ANN has also served as a prediction tool for other processes as well.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs have been used successfully as a predicting tool in all areas of textiles from fibre to complex composites. In textile spinning domain ANNs have been used to detect and classify trash particles in cotton web [6], control of draw frame sliver evenness and levelling action point from machine and material parameters [7], optimisation of spinning process at ring frame using draw frame parameters [8], the prediction of ring spun cotton yarn properties from HVI (high volume instrument) characteristics of fibres [9], comparison of ANN and regression models for yarn hairiness, evenness and tensile properties using fibre HVI properties, roving properties, yarn count and twist multiplier [10,11]. Apart from ring spinning ANN has also served as a prediction tool for other processes as well.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that we added yarn imperfection as a dependent new variable and obtained the optimal model for this important property. Most researchers considered only four yarn properties such as tenacity, breaking elongation, hairiness, and evenness of yarn (Majumdar & Majumdar, 2004;Majumdar et al, 2005;Ureyen & Gürkan, 2008a, 2008bUreyen & Kadoglu, 2006). As it might be expected, yarn strength is highly influenced by fiber strength and yarn count.…”
Section: Effect Of Raw Materials and Machine Factorsmentioning
confidence: 99%
“…The traditional standards of fibers, yarns, and fabric characterization should be revisited so that reliable and meaningful physical relationships between these characteristics can be established. Recently, Ureyen and Gürkan (2008a) developed statistical equations for the prediction of tensile properties of 100% cotton ring-spun yarn. They investigated the prediction of hairiness and unevenness of the yarn in the second part of their study (Ureyen & Gürkan, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using ANNs over other statistical methods-such as linear and nonlinear regression techniques-has been advocated on multiple occasions for various applications. For example, [20] made a comparison between the two techniques for the prediction of yarn tensile properties, [21] carried out the same comparison for Iran's annual electricity load, and [22] compared ANN with linear regression models for predicting hourly and daily diffuse fraction. All of them concluded that ANN was the better prediction approach.…”
Section: Introductionmentioning
confidence: 99%